Pengaruh Harga terhadap Keputusan Pembelian Konsumen pada Sagalas Coffee Panyabungan II Kabupaten Mandailing Natal - M. Wahyudi; Muhlisah Lubis; Rizka Ar Rahmah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the effect of price on consumer purchasing decisions at Sagalas Coffee Panyabungan II, Mandailing Natal Regency. The type of research used was quantitative research and involved a sample of 96 respondents using the Lemeshow formula. Data collection techniques are observation, documentation and distributing questionnaires. Data analysis techniques use validity tests, reliability tests, normality tests, heteroscedasticity tests, simple linear regression analysis tests and hypothesis tests. All research tests were carried out using the SPSS version 25 program. Price has a partial positive effect on consumer purchasing decisions at Sagalas Coffee Panyabungan II, Mandailing Natal Regency, indicated by an R value of 0.940 which is in the correlation interval 0.80 - 1.00 and an R value The square is 0.884 times 100% = 88.4% and the remaining 11.6% is influenced by other variables. In other words, there are still other variables that influence the consumer purchasing decision variable (Y) at Sagalas Coffee Panyabungan II. Based on the research results, it can be concluded that price has a positive and significant effect on consumer purchasing decisions, with a partial test value (t) of 26.789 and a ttable value of 1.661. So the tcount value is greater than ttable, namely 26.789, greater than 1.661 (26.789 > 1.661), which indicates that the first hypothesis, namely Ha, is accepted while H0 is rejected.